x+4=2(.4x+1.3)

Simple and best practice solution for x+4=2(.4x+1.3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+4=2(.4x+1.3) equation:


Simplifying
x + 4 = 2(0.4x + 1.3)

Reorder the terms:
4 + x = 2(0.4x + 1.3)

Reorder the terms:
4 + x = 2(1.3 + 0.4x)
4 + x = (1.3 * 2 + 0.4x * 2)
4 + x = (2.6 + 0.8x)

Solving
4 + x = 2.6 + 0.8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.8x' to each side of the equation.
4 + x + -0.8x = 2.6 + 0.8x + -0.8x

Combine like terms: x + -0.8x = 0.2x
4 + 0.2x = 2.6 + 0.8x + -0.8x

Combine like terms: 0.8x + -0.8x = 0.0
4 + 0.2x = 2.6 + 0.0
4 + 0.2x = 2.6

Add '-4' to each side of the equation.
4 + -4 + 0.2x = 2.6 + -4

Combine like terms: 4 + -4 = 0
0 + 0.2x = 2.6 + -4
0.2x = 2.6 + -4

Combine like terms: 2.6 + -4 = -1.4
0.2x = -1.4

Divide each side by '0.2'.
x = -7

Simplifying
x = -7

See similar equations:

| 15x^3-43x^2+28-4=0 | | 0=60x-3x^2 | | 3x+71=44 | | 4-7f=25 | | 27-3e=18 | | 10+4d=-26 | | x(x-2)=(x+2) | | 5x-13=4(2x-5) | | 5b+6-6b+2= | | 9x^2-32=40 | | 5.5q-4.6-6.6q=2.2-1.1q-2.4 | | 6.1x+3=5.1x | | 10(-2x+1)=-12(x+2)+34-8x | | 7x+9-8x+4=6x-7x-5 | | 7x+3=3+7x | | 7x+4y=18.25 | | 4(7x-2)+5(19-3x)=3(4x+3)-6 | | 2y+110+35=180 | | 5a+7=3a-15 | | 18x+4=58 | | (6x+7)-(4+5x)=12 | | (4*2k)+3k-2= | | 9+10r-2=9r+35-3r | | 48x^2+24x+3=0 | | x=-60+2s | | 2y+110+35=360 | | 3(x-1)-24=2(-1-x) | | 2w^2-3w-27=0 | | 4x+18=58 | | 2x+40=110 | | 10x+6=64 | | 3[3f+1]=7[2f+9] |

Equations solver categories